The influence of psychological capital towards work engagement among women employee in Johor Bahru corporate companies - Yuhanis Khalida A Rashid,; Fatin Amrina A Rashid,; Ana Haziqah A Rashid,; Nor Akmar Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigated how psychological capital influences work engagement among women employees in a corporate company. Data was collected using a self-assessment questionnaire from 102 women employees from two corporate companies in Johor Bahru district. The data were analyzed using the partial least squares structural equation modeling technique in SMARTPLS 3.2 software. Convergent and discriminant validity of the latent constructs were validated in this study. Overall, psychological capital has a moderate influence on work engagement among women employees in this corporate company, with R2 = 0.414. The structural model results revealed that resilience has a significant influence on work engagement. Findings show that resilience among women employees makes them more engaged with their work compared to self-efficacy, optimism and hope. Future studies should explore the difference between the influence of psychological capital between women and men towards their work engagement.